RNA Foci, CUGBP1, and ZNF9 Are the Primary Targets of the Mutant CUG and CCUG Repeats Expanded in Myotonic Dystrophies Type 1 and Type 2 - Jones, Karlie (American Society for Investigative Pathology, 2011)
Expansions of noncoding CUG and CCUG repeats in myotonic dystrophies type 1 (DM1) and DM2 cause complex molecular pathology, the features of which include accumulation of RNA aggregates and misregulation of the RNA-binding proteins muscleblind-like 1 (MBNL1) and CUG-binding protein 1 (CUGBP1). CCUG repeats also decrease amounts of the nucleic acid binding protein ZNF9. Using tetracycline (Tet)–regulated monoclonal cell models that express CUG and CCUG repeats, we found that low levels of long CUG and CCUG repeats result in nuclear and cytoplasmic RNA aggregation with a simultaneous increase of CUGBP1 and a reduction of ZNF9. Elevation of CUGBP1 and reduction of ZNF9 were also observed before strong aggregation of the mutant CUG/CCUG repeats. Degradation of CUG and CCUG repeats normalizes ZNF9 and CUGBP1 levels. Comparison of short and long CUG and CCUG RNAs showed that great expression of short repeats form foci and alter CUGBP1 and ZNF9; however, long CUG/CCUG repeats misregulate CUGBP1 and ZNF9 much faster than high levels of the short repeats. These data suggest that correction of DM1 and DM2 might be achieved by complete and efficient degradation of CUG and CCUG repeats or by a simultaneous disruption of CUG/CCUG foci and correction of CUGBP1 and ZNF9.